Role of ion conducting polymeric electrolyte in suppressing deterioration of cathode electrodes in dye-sensitized solar cells - Gurbuz, Osman; Gelir, Ali; Erden, Ibrahim; Firat, Yildiray; Okutan, Mustafa (ELSEVIER SCI LTD, 2016)
In this study, an ion conducting polymeric hydrogel (ICPH) is synthesized, characterized and used as a matrix for trapping the electrolyte solution to suppress the deterioration of cathode electrodes for dye sensitized solar cells (DSSCs). Polymeric hydrogels are synthesized as free radical cross-linking co-polymerization of acrylamide (AAm) and methylenebisacrylamide (BIS) as crosslink agent in slab forms with the same thickness. The polymer host is characterized by scanning electron microscopy (SEM). Impedance spectroscopy studies are carried out in the frequency range of 5 Hz-13 MHz at room temperature. It is observed that while the dielectric constant decreased, the loss tangents increased with increasing electrolyte content which is trapped in ICPH. The as-prepared ICPH/graphene electrodes, assembled with this material as cathode, are confirmed as substitution for platinum (Pt) counter electrode in DSSCs. The photovoltaic tests of the ICPH-DSSCs are carried out by the current-voltage (I-V) measurements and it is observed that ICPH-DSSC exhibited significantly enhanced electrical properties such as increased photovoltaic cell efficiency (PCE) which reached to 5.41% after using the ICPH. We predict that this work will open a way to fabricate the DSSC devices with a cathode electrode based on ion conductive polymeric hydrogels. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Ion conducting polymeric hydrogel; Dielectric constant; DSSC; Photovoltaic cell efficiency; Cathode electrode; ASYMMETRIC ZINC PHTHALOCYANINE; DIELECTRIC-PROPERTIES; BEHAVIOR; Chemistry; Engineering; Materials Science